Phytochemical Studies on Two Unexplored Endemic Medicinal Plants of India, Barleria terminalis and Calacanthus grandiflorus - Otari, Shreedhar S.; Patel, Suraj B.; Lekhak, Manoj M.; Ghane, Savaliram G. (Frontiers in Pharmacology, 2022)
Barleria terminalis Nees and Calacanthus grandiflorus (Dalzell) Radlk. are endemic medicinal plants of the Western Ghats of India. The aim of the present research work was to investigate phytochemical profile, potent bioactives using RP-HPLC, LC-MS and GC-MS and to evaluate their bioactivities. Acetone was found to be the best extraction medium for separating phytochemicals. Similarly, acetone and methanol extracts exhibited potential antioxidant properties. Ethanol extract of B. terminalis stem showed potent acetylcholinesterase (AChE) (89.10±0.26%) inhibitory activity. Inhibition of α-amylase (36.96 ±2.96%) activity was observed the best in ethanol extract of B. terminalis leaves and α-glucosidase inhibitory activity (94.33±0.73%) in ethanol extract of C. grandiflorus stem. RP-HPLC analysis confirmed the presence of several phenolic compounds (gallic acid, hydroxybenzoic acid, vanillic acid, chlorogenic acid and coumaric acid) and phenylethanoid glycoside (verbascoside). The highest phenolics content were observed in B. terminalis (GA (4.17±0.002), HBA (3.88±0.001), VA (4.54±0.001), CHLA (0.55±0.004) mg/g DW respectively). Similarly, LC-MS and GC-MS revealed the presence of phenolics, glycosides, terpenes, steroids, fatty acids, etc. Moreover, positive correlation between studied phytochemicals and antioxidants was observed in principal component analysis. Based on the present investigation, we conclude that B. terminalis and C. grandiflorus can be further explored for their active principles particularly, phenylethanoid glycosides and iridoids and their use in drug industry for pharmaceutical purposes.